"God's Absence During Trauma Took Its Toll": Dialogic Tracing of Literate Activity and Lifespan Trajectories of Semiotic (Un)becoming. (January 2022) - Ware, Ryan
Scholarship on trajectories of becoming with literate activities is of growing interest in Writing Studies, particularly in accounts of writing grounded in cultural-historical and dialogic approaches, and in lifespan accounts of writing. The research reported here contributes to those conversations by tracing trajectories of becoming that are dynamically nonlinear, necessarily messy, and predicated on exceptionally complex streams of times, places, life experiences, artifacts, and literate activities. I draw from one case study with Alex, once a deeply faithful Christian who, over complex trajectories of semiotic becoming, lost her faith and was left to make sense of drastic perspectival shifts, in large part, through literate activity. Weaving analyses of talk across 2 years, 15 interviews, and multiple texts and textual interactions, I trace a narrative of Alex's trajectories of unbecoming/becoming. I argue that Writing Studies needs flexible, theoretically grounded methods to trace becoming across lifespan trajectories and I address this imperative by showcasing one approach— dialogic animation protocols coupled with dialogic analyses .